Multi-omics analyses reveal the crosstalk between the circadian clock and the response to herbicide application in Oryza sativa - Chen, Ke; Su, Xiao; Yang, Haona; Peng, Yajun; Wu, Lamei; Zhao, Zhenghong; Lin, Tao; Bai, Lianyang; Wang, Lifeng (Frontiers in Plant Science, 2023)
Plants have evolved circadian clock systems that enable biological processes to occur in tandem with periodic changes in the environment. However, it is largely unknown whether crosstalk occurs between the circadian clock and the response to herbicide in rice. We identified 19 conserved rhythmic metabolites which were response to pesticide application and their metabolic abundance peaked mainly at ZT2 or ZT14-ZT18. We found a series of glyphosate, s-Metolachlor, fenclorim, metcamifen and GA3 response genes were expressed following stable circadian rhythms. In order to determine the patterns of their temporal expression, co-expression network analysis was done on 10,467 genes that were periodically expressed throughout a 24-hour period. Next, we identified 4,031 potential direct target genes of OsCCA1 in using DAP-seq data for OsCCA1. Of these, 339, 22, 53, 53 and 63 genes showed a response to glyphosate, s-Metolachlor, fenclorim, metcamifen and GA3 application, respectively. And they were mainly phased from dusk to midnight. Interestingly, we identified significant OsCCA1 binding peaks in the promoter regions of four herbicide resistance genes, including OsCYP81A12, OsCYP81E22, OsCYP76C2, and OsCYP76C4. Finally, we found that herbicide application could affects the expression of some of the central oscillator genes of the rice circadian clock. Here, we used multi-omics data to reveal the crosstalk between the circadian clock and herbicide response processes at the epigenomics, transcriptome, and metabolome levels in rice. This work will serve as a theoretical guide for identifying rhythmic herbicide targets, leading to the creation of new herbicides or the breeding of crops resistant to herbicides.